A novel research on behavior of zinc ferrite nanoparticles in different concentration of poly(vinyl pyrrolidone) (PVP) - Mohamed Kamari, Halimah; Naseri, Mahmoud Goodarz; Saion, Elias (MDPI, 2014)
Zinc ferrite nanocrystals were prepared from an aqueous solution containing metal nitrates and various of concentrations of poly(vinyl pyrrolidone) (PVP), i.e., 0, 15, 40, and 55 g/L, as a capping agent. To stabilize the particles, they were thermally treated at 873 K, as an optimum calcination temperature. The behaviors of the polymeric precursor were analyzed by use of simultaneous thermo-gravimetry (TG) and derivative thermo-gravimetry analyses (DTG). The presence of the crystalline phase in each sample was confirmed by X-ray diffraction (XRD) analysis. The average particle size and the morphology of the nanoparticles were determined by transmission electron microscopy (TEM), and these parameters were found to differ at various concentrations of PVP. Fourier transform infrared spectroscopy (FT-IR) confirmed the presence of metal oxide bands for all the PVP concentrations and confirmed the absence of organic bands for PVP concentrations less than 55 g/L. Measurements of the magnetization value of the zinc ferrite nanoparticles were obtained at room temperature by using a vibrating sample magnetometer (VSM), which showed that, in the absence of PVP, the sample exhibited a paramagnetic behavior while, in the presence of PVP, samples have a super-paramagnetic behavior.